2014
DOI: 10.1002/jbm.b.33226
|View full text |Cite
|
Sign up to set email alerts
|

Study on the use of 3‐aminopropyltriethoxysilane and 3‐chloropropyltriethoxysilane to surface biochemical modification of a novel low elastic modulus Ti–Nb–Hf alloy

Abstract: A biocompatible new titanium alloy Ti–16Hf–25Nb with low elastic modulus (45 GPa) and the use of short bioadhesive peptides derived from the extracellular matrix have been studied. In terms of cell adhesion, a comparative study with mixtures of short peptides as RGD (Arg‐Gly‐Asp)/PHSRN (Pro‐His‐Ser‐Arg‐Asn) and RGD (Arg‐Gly‐Asp)/FHRRIKA (Phe‐His‐Arg‐Arg‐Ile‐Lys‐Ala) have been carried out with rat mesenchymal cells. The effect of these mixtures of short peptides have already been studied but there are no compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Silane modifications have previously been proven to be a suitable approach to enrich a surface with a chemical group of interest, that can subsequently provide a level of control over cellular responses . To date the results from these experiments have been variable, this is due to a lack of knowledge concerning the different parameters namely chain length associated with specific silane chemistry, and the resulting properties of the silane monolayer which is presented to the cells, and a thorough investigation of the resultant material properties at the sub‐micron scale.…”
Section: Discussionmentioning
confidence: 99%
“…Silane modifications have previously been proven to be a suitable approach to enrich a surface with a chemical group of interest, that can subsequently provide a level of control over cellular responses . To date the results from these experiments have been variable, this is due to a lack of knowledge concerning the different parameters namely chain length associated with specific silane chemistry, and the resulting properties of the silane monolayer which is presented to the cells, and a thorough investigation of the resultant material properties at the sub‐micron scale.…”
Section: Discussionmentioning
confidence: 99%
“…22,47 In this regard, APTES has been extensively used for surface functionalization purposes and demonstrated its suitability for the immobilization of bioactive molecules onto Ti 22 and TiNbHf alloy. 48 Moreover, in a recent study we demonstrated that the use of APTES provides a more homogenous layer of biomolecule attachment in both Ti and TiNbHf alloy compared to physisorption. 49 Hence, in the present work APTES was chosen as linker molecule to immobilize the different bioactive molecules onto a recently developed low modulus TiNbHf alloy.…”
Section: One Approach To Improve Osseointegration In Metallic Implantmentioning
confidence: 93%
“…Aminosilanes are used as precursors in this procedure because they are able to bond with hydroxyl groups which may be induced on the oxidized surface of metals [14,15] and, in particular, may be used to functionalize titanium and its alloys [16][17][18][19]. In turn, the resulting amino groups of the functionalized surface are capable of binding themselves to a wide range of biomolecules [20].…”
Section: Introductionmentioning
confidence: 99%